INDOOR LOCALIZATION USING ACCELEROMETER AND GYROSCOPE SMARTPHONE BASED - Anggreini Intan Permata Sari; Arkham Zahri Rakhman (Jurnal Teknik Informatika (Jutif), 2021)
Indoor localization is one of the more accurate technologies to be used to determine indoors or buildings. Pedestrian Dead Reckoning (PDR) is a method of determining the user's position by adding a method that occurs to a known initial position. The displacement that occurs is estimated with the help of an accelerometer sensor attached to the user as a step detector and to determine the direction towards the user using a gyroscope sensor. System testing is carried out in the Institut Teknologi Sumatera’s campus environment on the 2nd floor of Building C and D. The results from the detection of steps get an error rate of 1.13% using a threshold of 0.8.